Four Hundred Fifty Years of the Foundation of the National University of San Marcos - Garmendia, Fausto (2001)
The San Marcos was founded shortly after the beginning of the conquest of Peru, in an environment characterized by irrepressible ambition for wealth of the conquerors and of the trustees, together with exploitation, abuse and merciless death of native heirs of the Inca Empire, by his pure inhuman dye moved to a religious group to denounce these facts and raise the cultural status of Spaniards, Creoles, mestizos and Indians. The work of Bartolomé de las Casas, who, moved by a judgment of wisdom Ecclesiastes-book of the Old Testament that says "he who offers sacrifice of the property of the poor is like the one slaughters a child before It is well known the father ... "- donated their property in an act of humanitarian release.